Southeast Asia and the rise of China the search for security - Storey, Ian 1970- (Routledge security in Asia series, 2011)
Since the early 1990s and the end of the Cold War, the implications of China's rising power have come to dominate the security agenda of the Asia-Pacific region. Although China's prioritization of economic development has created many valuable trade and investment opportunities, and encouraged China's gradual integration into the international community, economic growth is enabling China to modernize its armed forces, which, if present trends continue, will soon be among the largest and most powerful in the region. How China will flex its increased political, economic and military might is a key question for all China's neighbors. This book examines ASEAN-Chinese relations over recent years, showing how worries about China's developing role have been a significant factor in shaping the nature of ASEAN and its policies. The book includes a discussion of economic relations between China and the different ASEAN countries, an examination of how external powers have influenced the regional security environment, and an assessment of how China-ASEAN relations might develop over the next few decades against a backdrop of rising Sino-US competition.